Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Salale University - International Livestock Research Institute; Salale University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Salele University. On September 16, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Genanew Gofe, President of Salale University.